2014
DOI: 10.1302/0301-620x.96b6.33000
|View full text |Cite
|
Sign up to set email alerts
|

The frequency of sequelae of slipped upper femoral epiphysis in cam-type femoroacetabular impingement

Abstract: Slipped upper femoral epiphysis (SUFE) is one of the known causes of cam-type femoroacetabular impingement (FAI). The aim of this study was to determine the proportion of FAI cases considered to be secondary to SUFE-like deformities. We performed a case-control study on 96 hips (75 patients: mean age 38 years (15.4 to 63.5)) that had been surgically treated for FAI between July 2005 and May 2011. Three independent observers measured the lateral view head-neck index (LVHNI) to detect any SUFE-like deformity on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 57 publications
(60 reference statements)
0
5
1
Order By: Relevance
“…A prevalence of 13% was found for healthy young adults [9]: 35% to 68% in hips with osteoarthritis requiring THA [6,14] and 8% in anatomic specimens [7]. The only study investigating prevalence in hips with cam-type FAI without advanced osteoarthritis reported a prevalence of 44%, which is higher than in our cohort [15]. The reason for this difference might be related to the use of a single parameter based only on 2-D radiographs in other studies.…”
Section: ) (B)contrasting
confidence: 56%
See 2 more Smart Citations
“…A prevalence of 13% was found for healthy young adults [9]: 35% to 68% in hips with osteoarthritis requiring THA [6,14] and 8% in anatomic specimens [7]. The only study investigating prevalence in hips with cam-type FAI without advanced osteoarthritis reported a prevalence of 44%, which is higher than in our cohort [15]. The reason for this difference might be related to the use of a single parameter based only on 2-D radiographs in other studies.…”
Section: ) (B)contrasting
confidence: 56%
“…The four study groups differed in terms of age at the acquisition of the MRI, weight, and body mass index (BMI) ( Table 1). The normal group showed a decreased age (17 ± 2 [range, [15][16][17][18][19][20] years) compared with the other study groups (mean age ranging from 24 to 25 years; p ranging from \ 0.001 to 0.002). In the normal group, both weight (66 ± 14 [48-95] kg) and BMI (22 ± 3.4 [18][19][20][21][22][23][24][25][26][27][28] kg/m 2 ) were decreased compared with the idiopathic cam (p = 0.028 and p = 0.002, respectively) and slip-like group (both p = 0.001; Table 1).…”
Section: Methodsmentioning
confidence: 77%
See 1 more Smart Citation
“…However, some authors believe it useful and even superior to other radiographic incidences for FAI [12,16]. Several studies have demonstrated the values of interest [2,4,5,[17][18][19]. One of its advantages is that there is no accurate coding for the classic FL.…”
Section: Discussionmentioning
confidence: 99%
“…Slipped capital femoral epiphysis has been suggested to be one of the etiologic factors for cam-type impingement (82). Prevalence of a sliplike morphology in primary cam deformity was reported to be around 12% femur owing to a focal or general acetabular overcoverage.…”
Section: State Of the Art: Hip Imaging In Athletes Agten Et Almentioning
confidence: 99%